Informality and Aggregate Productivity : The Case of Mexico - Alvarez, Jorge; Ruane, Cian. (Washington, D.C. : International Monetary Fund, 2019)
We assess the aggregate productivity impact of distortions arising from labor regulations in Mexico and how they interact with informality. Using employment surveys and a firm-level economic census, we document a number of novel features about informal firms in Mexico. We then construct and estimate a model of heterogeneous firms and endogenous informality to study the micro and macro impacts from various policy reforms. Some reforms may have large impacts on informal employment but small impacts on aggregate productivity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Nepal